Health, illness and healthcare-seeking behaviour of the street dwellers of Dhaka City, Bangladesh: qualitative exploratory study. Issue 10 (7th October 2020) - Tune, Samiun Nazrin Bente Kamal; Hoque, Roksana; Naher, Nahitun; Islam, Nazia; Mazedul Islam, Md.; Ahmed, Syed Masud
Abstract : Objective: This study explored the illness experiences and healthcare-seeking behaviour of a cross-section of street dwellers of Dhaka City for designing a customised intervention. Design: A qualitative exploratory study of a sample of street dwellers of Dhaka City. Setting: Samples were taken from three purposively selected spots of Dhaka City with a high concentration of the target population. Participants: Fifteen in-depth interviews and six informal group discussions with 40 street dwellers (≥18 years), and key informant interviews with service providers (n=6) and policymakers (n=3) were conducted during January–June 2019 to elicit necessary data. Primary outcome measures: Qualitative narrative of illness experiences of the sampled street dwellers, relevant healthcare-seeking behaviour and experiences of interactions with health systems. Results: We focused on three main themes, namely, reported illnesses, relevant healthcare-seeking behaviour and health system experiences of the street dwellers. Findings reveal that most of the street dwellers suffered from fever and respiratory illnesses in the last 6 months; however, a majority did not visit formal facilities. They preferred visiting retail drug shops for advice and treatment or waited for self-recovery. Formal facilities were visited only when treatment from drug shops failed to cure them or they suffered serious illnesses or traumatic injury. The reproductive-age women did not seek pregnancy care and most deliveries took place in the street dwellings. Lack of awareness, financial constraints and fear of visiting formal facilities were some of the reasons mentioned. Those who visited formal facilities faced barriers like the cost of medicines and diagnostic tests, long waiting time and opportunity cost. Conclusions: The street dwellers lacked access to formal health systems for needed services as the latter lags far behind to outreach this extremely vulnerable population. What they need is explicit targeting with a customised package of services based on their illness profile, at a time and place convenient to them with minimum or no cost implications.